2018
DOI: 10.18502/ijml.v5i4.158
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Characterization of Dominant Serovars of Listeria Monocytogenes Strains Isolated from Spontaneous Human Abortion in Tehran

Abstract: Background and Aims: Assessment of the extend role of dominant serotyprs of Listeria monocytogenes in spontaneous abortions, using isolation methods and PCR(Polymerase Change Reaction) analysis for the presence of dominant serotypes such as 1/2a, 4b. Materials and Methods: A total of 258 samples comprising placental bits, vaginal swabs and blood were collected from out of 123 patients with spontaneous abortion. Listeria monocytogenes was identified and confirmed by culture, biochemical, serological tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Whereas, Kaur et al ( 11 ) found that 2 (50%) L. monocytogenes isolates carried all genes of this research plus iap gene. Rezaei et al ( 29 ) documented the existence of the hlyA gene in all L. monocytogenes isolates with spontaneous abortions. On the other hand, the presence of hlyA gene was detected in only 2 (40%) out of five L. monocytogenes isolates while 3 lacked this gene ( 30 ) probably due to mutation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, Kaur et al ( 11 ) found that 2 (50%) L. monocytogenes isolates carried all genes of this research plus iap gene. Rezaei et al ( 29 ) documented the existence of the hlyA gene in all L. monocytogenes isolates with spontaneous abortions. On the other hand, the presence of hlyA gene was detected in only 2 (40%) out of five L. monocytogenes isolates while 3 lacked this gene ( 30 ) probably due to mutation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%